Fear, Soft Propaganda, and the Demand for Government Intervention: Quasi-Experimental Evidence from Russia - Ekaterina Borisova; Timothy Frye; Koen Schoors; Vladimir Zabolotskiy; Nikita Zakharov (CESifo GmbH, 2025)
We explore the impact of fear on demand for government intervention. Our empirical strategy takes advantage of a unique quasi-experiment: During our survey in Russia, a very popular television program misreported the riskiness of the Covid-19 virus, thereby providing short-term exogenous variation in the fear of infection. Using a shift-share instrument based on this media intervention, we estimate a causally positive effect of fear on popular approval of a variety of government interventions. The magnitudes of this effect are remarkable, with a one-standard-deviation change in fear explaining as much as 77-103 percent of a standard deviation in our aggregate measure of demand for regulation, and 99-167 percent and 85-96 percent of a standard deviation in obligatory mask wearing and stay-home orders, respectively. However, fear had little impact on demand for interventions unrelated to the virus, such as censorship and housing policy. We explore potential mechanisms and establish that fear heightens perceptions of noncompliance with safe behaviour by others — a mechanism in line with a neoclassical view that free-riding concerns increase calls for government intervention. Our study informs debates on the demand for regulation, the role of emotions in shaping policy preferences, and the impact of media on political attitudes.
Keywords: D72; D91; H12; I12; I18; 330; demand for state intervention; soft propaganda; fear; Russia; Covid-19.